Settler-Colonial Violence, Primitive Accumulation and Australia's Genocide. (1st October 2018) - Michael Grewcock
Abstract : This article explores ways in which state crime theory, which is predominantly based on contemporary conceptions of human rights, might be applied to settler-colonial violence and the forced dispossession of the land from Indigenous peoples. The Australian state was established through the foundational violence inherent to settler colonialism and the processes of primitive accumulation that underpinned it. This created the conditions for ongoing structural violence, inflicted through a continuum of criminogenic, arguably genocidal state practices designed to disrupt – if not eliminate – the social worlds and collective identities of Indigenous peoples. These practices have been normalized through Australian nationalist ideology and its associated narratives of progress, democracy and the rule of law. Theories of state crime need to break from these normative narratives to make sense of the criminogenic nature of settler colonialism.